Diamond-Based Thin Film Bulk Acoustic Wave Resonator for Biomedical Applications - Zalazar, Martin (2013)
Nowadays it is in constant growing the development of thin film bulk acoustic resonators. If the piezoelectric material is going to be implanted in the human body, an important requirement is the biocompatibility of the implant. In this regard, Aluminum Nitride (AlN) has emerged as an attractive alternative for use in biomedical MicroElectroMechanical Systems. Ultrananocrystalline Diamond (UNCD) is a promising material to be used in biomedical applications, due to its extraordinary mulifunctionality; it is exceptional for implantable medical devices requiring stringent biological performance. Since both UNCD and AlN films can be processed via photolithography processes used in microfabrication, the integration of UNCD and AlN films provides the bases for developing a new generation of biocompatible Bio-MEMS/NEMS. Research and development was conducted to produce implantable MEMS devices: Pt/piezoelectric AlN/Pt layer heterostructure was grown and patterned on the UNCD membrane with a Ti adhesion layer. By applying voltages between the top and bottom Pt electrodes layers the piezoelectric AlN layer is energized. The feasibility of the fabrication of biocompatible AlN/diamond-based FBAR structure has been demonstrated.